Plea for routine endoscopic tracheostomy tube adjustment - Otto, Bettina; Lindemann, Regina; Kirsch, Holger; Schmid, Matthias; Vatter, Hartmut; Braun, Christiane (Frontiers in Rehabilitation Sciences, 2025)
IntroductionTracheostomy is one of the standard procedures in intensive care medicine. In the context of tracheostomy tube-, dysphagia- and decannulation management the selection of the appropriate tracheostomy tube model (angle, diameter, length) is crucial for the proper placement in the trachea. In spite of recent guidelines mentioning endoscopic control of the tube placement as a useful measure, data regarding the proper placement are rare in the present literature. Therefore, the aim of the present study was to investigate the accuracy of tracheostomy tube placement in patients admitted to our early neurological rehabilitation center.MethodsWe performed a retrospective single-center analysis of all patients with tracheostomy tube admitted to our early neurological rehabilitation center between 12/2022 and 01/2024. We analyzed the frequency, type and extent of injuries caused by a suboptimal placement of the tracheostomy tubes. The location of the tubes was routinely controlled endoscopically upon admission. In total 327 tracheoscopies were carried out. Clinical characteristics were collected in all patients and the endoscopic results were divided into malpositioned tracheostomy tubes (non-central tube position, often causing mucosal lesions, ulcer, bleeding) vs. well-positioned (central or almost central) tubes. The association between the quality of the tracheostomy tube placement and the characteristics age, gender, main diagnosis, tracheostomy procedure, time until initial endoscopic control of tracheostomy tube fitting after admission and after tracheostomy were analyzed using a logistic regression model.ResultsA total of 214 examinations (65%) revealed a malpositioned tracheostomy tube. In 19% of the carried out tracheoscopies (327), manifest injuries were already detectable (mucosal lesion, ulcer, bleeding). 113 examinations (35%) showed an acceptable tube placement. We found no association between the quality of the tracheostomy tube position and gender, age, main diagnosis, time until initial endoscopic control of tube fitting or type of tracheostomy.DiscussionSince we found a high percentage of suboptimal tracheostomy tube positions (65%), an increased risk of complications can be assumed. With a view to the most relevant late complication of tracheal stenosis, there is agreement that the fundamental lesion begins with mucosal ulceration, which we found in 19% of the investigations. Therefore, the present data strongly suggest that a routine endoscopic control of tracheostomy tube placement should be firmly implemented into the routine tracheostomy tube management. Our data further suggest that the supply with tracheostomy tubes needs to be optimized.